Explaining male body attitudes: the role of early peer emotional experiences and shame - Oliveira, Sara (2018)
The current study tested a path model that examined the association between early emotional experiences with peers and male body attitudes and whether general feelings of shame and body-focused shame mediate this relationship, while controlling for the effect of Body Mass Index. The sample comprised 241 men from the general community, aged from 18 to 60, who completed an online survey. Correlation analyses showed that the recall of positive early emotional experiences with peers is inversely linked to shame and negative body attitudes. Path analysis results indicated that early emotional experiences with peers had a direct effect on external shame, and an indirect effect on male negative body attitudes mediated by external shame and body-focused shame. Results confirmed the plausibility of the tested model, which accounted for 40% of the variance of male body attitudes. Findings suggested that men who recall fewer positive early peer emotional experiences tend to perceive that they are negatively viewed by others and present more body image-focused shame experiences. This in turn seems to explain a negative self-appreciation of one´s muscularity, body fat and height. This study contributes to a better understanding of male body attitudes. Findings suggest that the link between early emotional experiences and male body attitudes may depend on the experience of shame feelings and, particularly, on the extent to which one’s body image becomes a source of shame. These data support the relevance of addressing shame experiences when working with men with body image related-difficulties.